Pelatihan dan Pendampingan Komunitas Kesusteran ALMA, Bandung, untuk Memanfaatkan Limbah Minyak Rumah Tangga sebagai Bahan Baku Pembuatan Lilin - Kevin Cleary Wanta1; Cherish Rikardo; Loren Pratiwi; Anastasia Prima Kristijarti; Ceicalia Tesavrita (Journal of Appropriate Technology for Community Services, 2024)
Used cooking oil or commonly called used minyak jelantah is classified as waste that can pollute the environment. For this reason, this waste cannot be disposed directly into the environment. One way to process this waste is to recycle it, or to make other products that are more useful and valuable, such as candles from used cooking oil. This community service activity consist of, socialization, training and assistance for making candles from used cooking oil for the ALMA Sisters community: Bhakti Luhur Orphanage, Bandung. This activity was successful according to plan and the most important thing is that through this activity, there was success which had a positive impact on service partners. This activity is considered useful and provides new knowledge for partners. Moreover, with the help of tools and materials for producing candles from used cooking oil provided, the partners were able to produce a thousand candles which were ready to be marketed. This service activity will not stop with training and mentoring activities only. In the future, the service team will continue to train and assist partners, especially in terms of marketing, packaging and production of other products using used cooking oil as raw material.